Optimal residential load scheduling with price prediction - Ong, Dennis Guo Yao (Nanyang Technological University, 2021)
The objective of this report is to study and design an optimal load residential load scheduling scheme. As the technologies are getting more advanced, the traditional power grid is slowly transitioning into a smart grid. With the introduction of open electricity market, consumers are encourage to participate so that they can reduce their electricity bills as well as their load demands. Therefore, studies on different topics such as smart grid, demand side management, demand response and electricity price forecasting models are conducted to understand more about the advantages of real-time electricity pricing models and benefit from them. Finally, an optimal residential load scheduling scheme is designed and studied which hopefully will reduce the residential load demands and electricity bills.